The genetic architecture of complex traits: lessons from Drosophila - Mackay, Trudy (Henry Stewart Talks, 2008)
Complex traits, Identifying multiple genes and environmental risk factors, Nature of genetic variation affecting complex traits, Drosophila as a model system, P-element mutagenesis, Whole genome transcript profiles of genetically divergent strains, QTL mapping, Association mapping, Large numbers of loci, Pleiotropic effects on multiple traits, Sex, environment and genetic background dependent effects
Reviewed at 2018/05/31